THE EFFECT OF JIGSAW TECHNIQUE ON STUDENTS’ WRITING SKILL - Forsia, Lastry (FKIP, UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, 2021)
This research was to understand whether there is a major effect of Jigsaw technique on improving students’ writing ability to write down a narrative text at the tenth grade at SMAN 15 Tangerang. This research used quantitative method with quasi experimental design. The population of the research was the tenth grade that consisted of X.1-X.8. Both of classes were selected into two classes with purposive sampling, one class as experiment class and one class else as control class because the comparison result among both of class. They were X-8 as experiment class and X-7 as controlled class. The data was collected by the pre-test, treatment and post-test. The data was analyzed by using t-test formula. The results of the research showed that t count (2,21) was above than ttable (1,67). It might be concluded that there was a significance effect of Jigsaw Technique in teaching writing narrative text on the students’ writing ability. Then, Jigsaw technique could give assistance students to focus and elaborate their product writing. Keywords: Jigsaw, quasi experiment research, Writing Skill